HUBUNGAN PRAKTEK KESELAMATAN PASIEN PADA TINDAKAN PEMBEDAHAN DENGAN SURGICAL SAFETY CHECKLIST WHO TERHADAP LUARAN KLINIS DI RSUD MUNTILAN KABUPATEN MAGELANG - , Yuniar; , Prof. dr. Adi Utarini, M.Sc.,MPH, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The number of surgery in the world is very large, almost double exceeds the birth rate per year. The high rate of complications and death due to surgery was supposed to be a global health concern. The incidence of undesirable post-surgical hospital almost half are preventable. The World Health Organization to introduce surgical safety checklist that aims to improve patient safety and decrease complications and death due to surgery. Objective: measure the relationship of patient safety practices by WHO surgical safety checklist on the incidence of clinical outcomes post surgery. Method: This type of research is an observational prospective longitudinal research design. The subjects of this study is all performed major surgery in the period April to June 2013 in the Central Surgical Installation Muntilan Hospital Magelang District. The observation done with instruments WHO surgical safety checklist and assessment of clinical outcomes up to 30 days post surgery. The data were analyzed with the approach of univariate, bivariate and multivariate. Results and Discussion: Complications occurred in 32 subjects (12.5%), the most complications is surgical site infection (SSI) 27 subjects (10.5%). The Result of multivariate analysis on factors surgery obtained factors were significantly related to the occurrence of clinical outcomes that length of stay in hospital (RR = 3.98, 95% CI: 1.78 to 8.89585) (p = 0.001). On multivariate analysis on SSC, subjects who did not receive prophylactic antibiotics before surgery has a significant risk of 2.59 times compared to the SSI subjects who received antibiotic prophylaxis (RR = 2.59, 95% CI: 1.06 to 6.28) (p = 0.036). Conclusion and Recommendation: there is a relationship between the practice of surgery with the WHO surgical safety checklist with the clinical outcomes of surgical site infection. Need to do the implementation of WHO surgical safety checklist on any of surgery in the hospital.